Real-time shader programming covering DirectX 9.0 - Fosner, Ron. (San Francisco : Morgan Kaufmann Publishers, 2003)
Now that PC users have entered the realm of programmable hardware, graphics programmers can create 3D images and animations comparable to those produced by RenderMan's procedural programs-but in real time. Here is a book that will bring this cutting-edge technology to your computer. Beginning with the mathematical basics of vertex and pixel shaders, and building to detailed accounts of programmable shader operations, Real-Time Shader Programming provides the foundation and techniques necessary for replicating popular cinema-style 3D graphics as well as creating your own real-time procedural shaders. A compelling writing style, color illustrations throughout, and scores of online resources make Real-Time Shader Programming an indispensable tutorial/reference for the game developer, graphics programmer, game artist, or visualization programmer, to create countless real-time 3D effects. * Contains a complete reference of the low-level shader language for both DirectX 8 and DirectX 9 * Provides an interactive shader demonstration tool (RenderMonkeyTM) for testing and experimenting * Includes a CD ROM containing all shader examples, source code, and tools, plus the DirectX SDK * Maintains an updated version of the detailed shader reference section at www.directx.com * Teaches the latest shader programming techniques for high-performance real-time 3D graphics.
Preface -- Chapter 1: Introduction -- Chapter 2: Preliminary Math -- Chapter 3: Mathematics of Lighting and Shading Chapter 4: Introduction to Shaders -- Chapter 5: Shader Set Up in DirectX -- Chapter 6: Shader Tools and Resources -- Chapter 7: Shader Buffet -- Chapter 8: Shader Reference (Part I: Vertex Shader Reference and Part II: Pixel Shader Reference) References -- Index -- About the Author -- About the CD-ROM.
Includes bibliographical references and index.
Keywords: Computer graphics; Real-time data processing; Three-dimensional display systems; DirectX; Electronic books